Clinical Relevance of Calcifications in Osteosarcoma Lung Metastases: Correlations Among Radiological Patterns, Histological Subtypes, and Chemotherapy Responses - Paolo Spinnato; Mario Simonetti; Maria Carpenzano; Gabriele Bilancia; Nicola Marrone; Annamaria Chiesa; Maddalena Di Carlo; Emanuela Palmerini; Luca Cevolani; Marco Colangeli; Marco Gambarotti; Alberto Righi; et al. (Clinics and Practice, 2026)
Background/Objectives: Osteosarcoma is a rare malignancy and the most common primary malignant bone tumor. Metastases commonly affect the lungs and are associated with reduced life expectancy. Calcifications can be present within a metastatic nodule at baseline or can appear during follow-up. We aimed to assess the clinical significance of calcifications in lung metastases, particularly in relation to radiological pattern, histopathological subtype, and treatment response. Methods: A retrospective cohort of patients with osteosarcoma and lung metastases at diagnosis was evaluated for the period 2000–2018. The presence of calcifications inside pulmonary lesions on baseline lung CT and/or follow-up was assessed and recorded. Radiological data were then checked against histopathological data (i.e., osteosarcoma subtypes and chemotherapy response with necrosis percentage) and the radiological pattern of the primary tumor (i.e., osteolytic, sclerotic, or mixed pattern). Results: Of a cohort of 92 patients, 14 were excluded due to having no baseline or follow-up chest CT. Of the 78 patients with an osteosarcoma diagnosis, lung metastases at diagnosis, and chest CT who were enrolled (42 men and 36 women; mean age: 23.8 years [range, 6–73 years]), 70 (89.7%) had a baseline imaging study of the primary tumor (osteosarcoma). The presence of calcifications in lung metastases at both baseline and follow-up was significantly associated with the radiological pattern of the primary lesion (p < 0.0001). Calcifications were not present in the lung metastases of any of the 18 patients (0%) with a lytic radiological pattern at any stage, whereas all 32 patients (100%) with a purely sclerotic pattern had calcifications within lung metastases at baseline or during follow-up; of the 20 patients with a mixed radiological pattern, 11 (55%) had no calcifications and 9 (45.0%) had detectable calcifications. No statistically significant association was found between histopathological subtype and calcification. Osteoblastic osteosarcoma was more frequently associated with calcification (66.0%). During induction chemotherapy, five poor responders and three good responders (necrosis > 90%) developed calcifications (p = 0.72; OR = 0.67; 95% CI, 0.10–3.86). Conclusions: In patients with osteosarcoma, calcifications within pulmonary metastases are strongly associated with the radiological pattern of the primary tumor, and this association is greatest for a pure sclerotic pattern, followed by the mixed one. We found no statistically significant association between the occurrence of calcifications during follow-up and chemotherapy response measured by necrosis percentage of the surgical specimen in our limited cohort; further research is needed.